منازعات مجلس المنافسة في التشريع الجزائري - حاجي الطيب – سعد الدين عبد الرحمان (المسيلة, 2022)
يعد مجلس المنافسة إحدى سلطات الضبط الاقتصادي في الجزائر، والذي تم استحداثه سنة 1995في ظل الإصلاحات الاقتصادية التي شهدتها الجزائر أواخر الثمانينات وبداية التسعينات من القرن الماضي، حيث منح المشرِع الجزائري لمجلس المنافسة قدرا كبيرا من الاستقلالية وأناط به جملة من الوظائف منها التنازعية ومنها غير التنازعية، وذلك قصد تمكينه من الضبط الفعال للمنافسة داخل السوق بين مختلف المتعاملين الاقتصاديين فيه، و تجسيد مبدأ حرية المنافسة ومحاربة كل ممارسة من شأنها عرقلتها، باعتبار أن حرية المنافسة تعد من بين أهم المبادئ المصاحبة لنظام اقتصاد السوق. الكلمات المفتاحية: منازعات، مجلس المنافسة، التشريع الجزائري Summary: The Competition Council is one of Algeria's economic control authorities, which was established in 1995 in the light of economic reforms in Algeria in the late 1980s and early 1990s. The Algerian legislator granted the Competition Council a great deal of autonomy and was entrusted with, inter alia, contentious and non-contentious functions. in order to enable it to effectively control competition within the market between its various economic clients, Embodying the principle of freedom of competition and fighting any practice that obstructs it s economic system ", as freedom of competition was one of the most important principles accompanying the market economy system.
Keywords: منازعات، مجلس المنافسة، التشريع الجزائري